2021
DOI: 10.3389/fmolb.2021.652250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mRNA-, circRNA- and lncRNA- Associated ceRNA Networks and Potential Biomarkers for Preeclampsia From Umbilical Vein Endothelial Cells

Abstract: ObjectiveThe etiology and pathogenesis of preeclampsia (PE) remain unclear, and ideal biomarkers for the early detection of PE are scarce. The involvement of the competing endogenous RNA (ceRNA) hypothesis in PE is only partially understood. The present study aimed to delineate a regulatory network in PE comprised of messenger RNAs (mRNAs), circular RNAs (circRNAs), long non-coding RNAs (lncRNAs), and microRNAs (miRNAs) via ceRNA profiles from human umbilical vein endothelial cells (HUVECs) to further reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Two pieces of placental tissue (approximately 1 cm 3 each) were dissected from the maternal surface of the placentas (away from the umbilical cord attachment area, avoiding bleeding and calcification). Placental tissues were separated and stored at −80°C [ 24 ]. Preeclampsia was defined as hypertension with proteinuria (urinary protein > 300 mg/24 h) that occurred after 20 weeks of gestation [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pieces of placental tissue (approximately 1 cm 3 each) were dissected from the maternal surface of the placentas (away from the umbilical cord attachment area, avoiding bleeding and calcification). Placental tissues were separated and stored at −80°C [ 24 ]. Preeclampsia was defined as hypertension with proteinuria (urinary protein > 300 mg/24 h) that occurred after 20 weeks of gestation [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that BST2 expression was differentially expressed in human umbilical vein endothelial cells (HUVECs) between normal and PE pregnancies [ 24 ]. However, the expression of BST2 in the placenta of pregnant women with PE and its specific mechanism of action have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually diagnosed after week 20 of gestation and is characterized by maternal hypertension and proteinuria [ 14 ]. An increasing number of studies have been investigating PE etiopathogenesis, showing that ncRNAs, especially miRNAs [ 14 ], circRNAs [ 94 , 95 , 96 ], and lncRNAs [ 44 ] detectable in both maternal placenta and plasma, have a crucial role in endothelial angiogenic function and placentation [ 97 , 98 , 99 ].…”
Section: Ncrnas In Pregnancy Complications: Role Of Fetal Sexmentioning
confidence: 99%
“…Subsequently, we assessed the full texts of the remaining 48 articles and excluded 34 studies based on the exclusion criteria, including 7 not studies on circulating ncRNAs, 8 without clinical data to make a 2 × 2 contingency table and 8 studies that used ncRNAs for diagnosis. In total, 14 studies were ultimately included in this study [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The selection process ow chart of our study is presented in Fig.…”
Section: Literature Searchmentioning
confidence: 99%